The Qur'an and the Sunnah - Al-Faruqi, Ismail Raji (International Institute of Islamic Thought, 2014)
Without a doubt, the Qur'an is beautiful, indeed, the most beautiful literary composition the Arabic language has ever known. It signified the divine presence itself and commanded the greatest honor. The proof that the Qur'an was the word of God devolved upon the Qur'an itself. The Qur'an, Muhammad claimed with Qur'anic approval, indeed dictation, is so beautiful that it is inimitable; it is so inimitable that it is miraculous. It is therefore not the work of humans but of God. This character of the Qur'an is called its i'jaz. The Sunnah as concretization of the vision, or materialization of the ideal, translated theory into reality. In it, the values of Islam were given form and became alive. They throbbed with moving power. The Sunnah supplied the missing link between thinking and doing, between ideational apperception and action, between thought and life and history.